Who was Sacagawea?- Biography - Fradin, Dennis B.; Fradin, Judith Bloom; Taylor, Val Paul (New York : Grosset & Dunlap, 2002)
A brief biography of Sacagawea, the Shoshoni woman who accompanied explorers Lewis and Clark on their expedition in the early 1800s.
Keywords: Sacagawea -- Juvenile literature; Sacagawea; Shoshoni women -- Biography -- Juvenile literature; Shoshoni Indians -- Biography -- Juvenile literature; Shoshoni Indians -- Biography; Indians of North America -- Biography; Women -- Biography